2009
DOI: 10.1161/hypertensionaha.109.135947
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Endothelin 1 to the Vascular Effects of Diesel Exhaust Inhalation in Humans

Abstract: Abstract-Diesel exhaust inhalation impairs vascular function, and, although the underlying mechanism remains unclear, endothelin (ET) 1 and NO are potential mediators. The aim of this study was to identify whether diesel exhaust inhalation affects the vascular actions of ET-1 in humans. In a randomized, double-blind crossover study, 13 healthy male volunteers were exposed to either filtered air or dilute diesel exhaust (331Ϯ13 g/m 3 ). Plasma concentrations of ET-1 and big-ET-1 were determined at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 33 publications
4
25
1
1
Order By: Relevance
“…DE inhalation attenuates vasodilation in response to both endothelium-dependent and nitric oxide donor drugs, but not in response to vasodilators acting via smooth muscle cell receptors; a profile that is suggestive of NO scavenging by O 2 − free radicals (143,206). Exposure to C-DEAP is known to cause a compensatory increase and to eventually deplete antioxidant concentrations in respiratory tract lining fluids and pulmonary cells (207).…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…DE inhalation attenuates vasodilation in response to both endothelium-dependent and nitric oxide donor drugs, but not in response to vasodilators acting via smooth muscle cell receptors; a profile that is suggestive of NO scavenging by O 2 − free radicals (143,206). Exposure to C-DEAP is known to cause a compensatory increase and to eventually deplete antioxidant concentrations in respiratory tract lining fluids and pulmonary cells (207).…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…Chalk PM 2.5 could also stimulate alveolar macrophages to produce reactive oxygen species and cause oxidative stress and cytotoxicity (Zhang et al, 2015a, b). Although the adverse health effects of ultrafine particles remains uncertain, various experimental studies have indicated that human exposure to nanoparticles is related to cardiovascular diseases (Lucking et al, 2008;Langrish et al, 2009;Samet et al, 2009). According to Figs.…”
Section: Particle Size Distribution Of Chalk Dustmentioning
confidence: 99%
“…Using a randomized, double-blind, three-way crossover design, 19 healthy male volunteers (mean age, 25 AE 3 yrs) were exposed to filtered air, unfiltered dilute diesel engine exhaust, and dilute diesel engine exhaust during 1-hr periods of alternating moderate exercise and rest. These investigators assessed responses to a number of surrogate measures of adverse cardiovascular effects that they had previously shown to be affected by elevated whole-DE exposures without a particle trap in place, [82][83][84][85] including endothelial vasomotor and fibrinolytic function and ex vivo thrombus formation.…”
Section: Preliminary Findings From Humanmentioning
confidence: 99%